Enhancement in magnetoelectric coupling in PZT based composites. Issue 4 (May 2015) - Dipti; Juneja, J.K.; Singh, Sangeeta; Raina, K.K.; Prakash, Chandra
Abstract: Enhancement in the value of magnetoelectric (ME) coupling coefficient ' α ' can be observed when lead zirconate titanate (PZT) ferroelectric material near morphotropic phase boundary (MPB) is mixed with small amount of high resistive nickel substituted cobalt ferrite (CNFO) ferrite phase in comparison to pure cobalt ferrite (CFO). The composites are prepared by a solid state reaction method. The value of ' α ' was found to be 3 times (855 μV/(cm Oe)) in composites of PZT and CNFO as compared in composites of PZT and pure cobalt ferrite (298 μV/(cm Oe)). This enhancement in ' α ' can be correlated with increased electrical resistivity of CFO due to substitution of Ni at Co-site. Furthermore, to confirm the multiferroicity of the prepared samples structural, dielectric, ferroelectric and magnetic properties were also measured for prepared composites.